2016
DOI: 10.5194/hess-20-2135-2016
|View full text |Cite
|
Sign up to set email alerts
|

Sharing water and benefits in transboundary river basins

Abstract: Abstract. The equitable sharing of benefits in transboundary river basins is necessary to solve disputes among riparian countries and to reach a consensus on basin-wide development and management activities. Benefit-sharing arrangements must be collaboratively developed to be perceived not only as efficient, but also as equitable in order to be considered acceptable to all riparian countries. The current literature mainly describes what is meant by the term benefit sharing in the context of transboundary river… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 40 publications
(42 reference statements)
0
25
0
Order By: Relevance
“…Therefore, there is a consensus that cooperative water resources planning and management in a trans-boundary river basin can provide opportunities to increase water benefits [4][5][6][7][8]. Phillips et al [4] suggested a policy context for shared responsibility and an institutional framework for analyzing shared benefits resulting from the corporation between countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there is a consensus that cooperative water resources planning and management in a trans-boundary river basin can provide opportunities to increase water benefits [4][5][6][7][8]. Phillips et al [4] suggested a policy context for shared responsibility and an institutional framework for analyzing shared benefits resulting from the corporation between countries.…”
Section: Introductionmentioning
confidence: 99%
“…Leb [6] analyzed the dynamics of international cooperation and described the role of international law in achieving mutually beneficial relations. Jalilov et al [7] and Arjoon et al [8] used hydro-economic models to estimate the total economic benefits using various scenarios in trans-boundary river basin operations and provided an experimental case study on how the concept of benefit sharing could be used to motivate riparian countries to enhance their cooperation and develop shared water resources.…”
Section: Introductionmentioning
confidence: 99%
“…First, within the context of transboundary water management, benefit sharing has been suggested and promoted as a new way to seek cooperation between countries with competing interests by development-oriented agencies such as the World Bank, Swedish Ministry for Foreign Affairs, and Overseas Development Institute (e.g., [11,15,16,40]). The suggested concept has been picked up by a number of scholars, who developed models for different transboundary river basins around the world (e.g., [41][42][43][44]), and by donor community and basin management organizations, who actively promoted the approach in negotiations to foster cooperation between riparian states (e.g., [45][46][47]). Second, the conference of parties to the Convention of Biological Diversity (CBD) took active steps to establish a new international regime on access to genetic resources and benefit sharing (ABS), which resulted in adoption of the Nagoya Protocol in 2010 [20,48].…”
Section: Introductionmentioning
confidence: 99%
“…However, the resulting allocation strategy would imply an asymmetrical distribution of revenues causing equity issues. To deal with them, cooperation strategies should be explored using, for example, Game Theory (Madani, 2010;Madani and Hipel, 2011), and solved applying proper benefit-sharing mechanisms (Arjoon et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…However, this efficiency improvement is not symmetrically distributed, so equity issues may arise. These could be examined using, for example, Game Theory (Girard et al, 2016;Madani, 2010), and they could be addressed by employing benefit-sharing mechanisms (Arjoon et al, 2016).…”
Section: Limitations and Further Researchmentioning
confidence: 99%